The robust maximum principle : theory and applications - Boltyanski, Vladimir G. , 1925-; Poznyak, Alexander S. (Systems & control: foundations & applications, 2012)
Covering key areas of optimal control theory, this book uses new methods to set out a version of OCT's more refined 'maximum principle' aimed at solving the problem of constructing optimal control strategies for uncertain systems with some unknown parameters